Representation of Journalists' Professionalism in the Film a Taxi Driver - Maulidia Azwini Anzar; Kadek Dristiana Dwiviyani; Kheyene Molekandella Boer (Jurnal Indonesia Sosial Teknologi, 2024)
Film is a mass communication medium that combines audio, visuals, and narration to convey stories, and information, and serves as a medium of entertainment and education for the audience. One such film that provides both entertainment and historical education is A Taxi Driver, which falls under the genres of drama, history, and politics. This film is based on the true story of a taxi driver who inadvertently became involved in the Gwangju uprising of 1980 after helping a German journalist cover the events in Gwangju. The purpose of this research is to understand the representation of journalistic professionalism in the film A Taxi Driver according to the Code of Ethics of the International Federation of Journalists (IFJ) using a descriptive qualitative research method with Roland Barthes' semiotic analysis. The results of this study identify several scenes in the film A Taxi Driver that illustrate the articles of the International Federation of Journalists (IFJ) Code of Ethics through various actions of Peter, who plays the journalist. Among them: Article 1 "Respect for Truth" is reflected when Peter visits Gwangju to validate information from Reporter Lee. Article 2 "Freedom of the Press" is evident when Peter attempts to record events at the shooting site. Article 3 "Fair Methods to Obtain Information" is shown by his bravery in recording amid the riots. Article 8 "Transparency" is seen in Peter's promise to publish news about the chaos in Gwangju once he returns to Japan. Article 12 "Solidarity" highlights by his efforts to save Kim's life, compensate for the damage to Kim's taxi, and his desire to reunite with Kim to repay his kindness. Article 15 "Humanity" is demonstrated through Peter's actions of recording the bodies of Gu Jae-sik and the victims of military violence, as well as helping to evacuate the shooting victims.